(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
This study was conducted to assess cattle marketing practice in the crop-livestock production system areas of the highland, mid-altitude and pastoralists in the lowlands of Guradamole Woreda of Bale zone of Ethiopia. That is conducted from July 2015 to 2015 March. Cattle marketing practice were assessed based on market monitoring and questionnaire survey in each altitude. A total of 100 farmers were selected randomly from 10 peasant associations which are selected from each altitude based on proportion of peasant association in each altitude. Market monitoring was done at two livestock marketing places of Rayitu town and Jibri, which is capital city of Guradamole Woreda. Cattle marketing varied considerably across the peasant associations and marketing places. Cattle supplied to markets include calves, heifers, bulls and oxen, dry and lactating cows. Who often supply cattle to marketing places are farmers and pastoralists from Guradamole Woreda and neighboring ethnic societies. Livestock market infrastructure and management are among the key constraints to the development and sustainable management of livestock markets. Long trekking distances to markets are a significant impediment to pastoralists ability to profitably sell their cattle. During drought periods, animals lose weight on the journey to market, which significantly lowers their value. In some cases, animals are too weak to embark on the homeward journey, forcing producers to sell at very low prices. Poor and uneven access to market information remains a major constraint for market actors and producers in particular. Observations at market sites point to an imbalance in the bargaining power of traders and producers. Traders collude and jointly determine prices ahead of market day and producers have very little or no ability to negotiate prices. Int. J. Agril. Res. Innov. & Tech. 6 (2): 36-41, December, 2016